Amphiphilic Polymer Conetworks Based on Interconnected Hydrophobic Star Block Copolymers: Synthesis and Characterization. Issue 1 (April 2017) - Kepola, Eleni J.; Kyriacou, Kyriacos; Patrickios, Costas S.; Simon, Miriam; Gradzielski, Michael; Kushnir, Michelle; Wesdemiotis, Chrys
Summary: Herein we report on the preparation and structural characterization of six amphiphilic polymer conetworks (APCN) based on end‐linked amphiphilic "core‐first" star block copolymers, comprising methyl methacrylate and 2‐(dimethylamino)ethyl methacrylate as the monomer repeating units in the hydrophobic and hydrophilic blocks, respectively. The various APCNs differed either in the arm composition or in the arm molecular weight. APCN synthesis was accomplished via the one‐pot, sequential group transfer polymerization (GTP) of cross‐linker, hydrophobic monomer, hydrophilic monomer, and cross‐linker again. The soluble precursors to the APCNs, i.e., the star homopolymers, the star block copolymers and the initial cross‐linker cores, were characterized in terms of their composition, size and size dispersity. The degrees of swelling in tetrahydrofuran were found to increase with the molecular weight of the arms of the stars of the APCNs, whereas the degrees of swelling in water increased with the content in hydrophilic units in the arms of the constituting stars. Small‐angle neutron scattering (SANS) indicated that most APCNs nanophase separated in D2 O. The structure and size of the hydrophobic domains determined by fitting the SANS data to an appropriate model could be correlated with the molecular architecture of the APCNs. Finally, polarized light microscopy showed that all APCNs were birefringent both in water and in the dried state.